ANALISIS KEUNTUNGAN MEBEL KAYU KELAPA DI BLPT KAATEN KOTA TOMOHON PROVINSI SULAWESI UTARA - Fanty Falty Pelealu; Joachim N. K. Dumais; Audrey J. M. Maweikere (Sam Ratulangi University, 2018)
This study aims to determine the advantages of coconut wood furniture business at the BLPT Kaaten in Tomohon, North Sulawesi Province. This research was conducted for 3 months from February to April 2018. The data carried out in this study were primary data and secondary data. Primary data were obtained from interviews while secondary data were from the Kaaten BLPT in Tomohon City, North Sulawesi province. The results of the study showed that coconut wood furniture products at the Kaaten BLPT were unique in terms of the design and quality of the products produced. Products are designed according to the wishes of consumers and the quality of wood raw materials is processed to produce good quality wood. Total revenue of Rp. 86,900,000, - minus the total costs incurred in the amount of Rp. 43. 612,599, - the profit obtained from coconut wood furniture for the period of January - March 2018 is Rp. 37,287,401, -. The R / C value of this coconut wood furniture is 1.9, the coconut wood furniture business in the BLPT Kaaten is profitable.*jnkd*.